Desain Pembelajaran Berbasis Web Untuk Meningkatkan Kemampuan Bicara Bagi Anak Tuna Rungu di SDLB Futhiyyah Pati - Rois, Ahmad (AL-BURHAN, 2024)
This study aims to create a web-based learning design to improve speech skills in deaf children at SLB Futhiyyah Pati. The method used in this study is Research and Development (RD). The results of this study are 1) the realization of a valid web-based learning design. This is indicated by the results of expert validation showing a mean of 3.45 in the very valid/feasible category. Web-based learning design can be said to be effective in improving the speech skills of deaf children. This is indicated by the results of the p-value in the chi-square analysis which shows 0.05. and the applicability of the applied learning design is 89.83%.Keywords: Learning Design, Web, Deaf Kids